Copy number variants including RAS pathway genes—How much RASopathy is in the phenotype?. (14th May 2015) - Lissewski, Christina; Kant, Sarina G.; Stark, Zornitza; Schanze, Ina; Zenker, Martin
<x xml:space="preserve">Abstract</x> The RASopathies comprise a group of clinically overlapping developmental syndromes the common pathogenetic basis of which is dysregulated signal flow through the RAS‐MAPK pathway. Mutations in several components or modifiers of the pathway have been identified in Noonan syndrome and related disorders. Over the past years copy number variants (CNVs) encompassing RAS pathway genes (PTPN11, RAF1, MEK2, or SHOC2) have been reported in children with developmental syndromes. These observations raised speculations that the associated phenotypes represent RASopathies, implying that the increased or reduced expression of the respective RAS pathway component and a consecutive dysregulation of RAS pathway signalling is responsible for the clinical picture. Herein, we present two individuals and three of their relatives harboring duplications of either 3p25.2 including the RAF1 locus or 19p13.3 including the MEK2 locus. Duplication carriers exhibited variable clinical phenotypes including non‐specific facial dysmorphism, short stature, and learning difficulties. A careful review of the literature supported the impression that phenotypes associated with CNVs including RAS pathway genes commonly share non‐specific symptoms with RASopathies, while the characteristic "gestalt" is lacking. Considering the known molecular pathogenesis of RASopathies, it is questionable that a modest increase in the expression of a functionally normal signaling component can mimic the effects of a qualitatively abnormal (hyperactive) mutant protein. We thus argue that current empirical and biological evidence is still insufficient to allow the conclusion that an altered copy number of a RAS pathway component is indeed the mechanism that is critical for the phenotype associated with CNVs including RASopathy genes. © 2015 Wiley Periodicals, Inc.